2013
DOI: 10.1109/jsen.2013.2252164
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Functionalized Nanosystems for Multimodal Molecular Sensing and Imaging in Medicine

Abstract: Successful employment of multimodal molecular imaging for cancer targeting entails the development of safe nanoparticle contrast agents (NPCAs), detects at least by two nonionizing imaging techniques. This paper presents a quantitative assessment of the effectiveness of both pure silica nanospheres (SiNSs) and composite silica/superparamagnetic NPCAs as scatterers for low-frequency diagnostic ultrasound (US) (3 MHz) in very low range of concentrations (1.5-5 mg/mL). Iron oxide (IO) and FePt-IO nanocrystals are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Our results regarding the backscatter signal related to HNTs identified level of enhancement levels comparable to those obtained with other nanoparticle contrast agent under similar experimental conditions [11], [14], [15], although direct terms of comparison with other HNT based research studies are still unavailable due to the relatively recent popularity HNT are experiencing for clinical applications.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our results regarding the backscatter signal related to HNTs identified level of enhancement levels comparable to those obtained with other nanoparticle contrast agent under similar experimental conditions [11], [14], [15], although direct terms of comparison with other HNT based research studies are still unavailable due to the relatively recent popularity HNT are experiencing for clinical applications.…”
Section: Discussionsupporting
confidence: 75%
“…Conversely to those nanoparticle contrast agents characterized by geometrical symmetry [11], [14], [15], the elongated structure and the nonhomogeneous length of the HNTs may cause such nonlinearity of their acoustic behavior, although the analysis of a large population of frames and the realization of triplicate samples for each concentration aimed to reduce the effect of such anisotropies on the backscatter signals. Therefore, among the studied concentrations, 3 mg/mL could rather represent the critical value at which the US signal attenuation, due to the shielding by HNTs included in the phantoms, balances the US enhancement; on the other hand, the shielding effect appeared overcome when the highest concentration is employed with a signal increment between 3 and 5 mg/mL lower than that registered between 0 and 1.5 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the desired amount of HNTs (purified dehydrated HNTs were obtained from Applied Minerals, Inc) were added to agarose solution in a vial, and the mixture was sonicated for 30 seconds; 1 mL of the obtained suspension was quickly poured into the Eppendorf tube. Since the majority of the HNTs consists of cylindrical tubes of 40-50 nm diameter and length of 0.5 to 2 µm polydisperse in length, empty lumen of the halloysite with 15-20 nm diameters [4], the adopted amount of HNTs were quantified in mg/mL and corresponded to 1.5, 3 and 5 mg of HNT in 1 mL of agarose gel, according to a previously validated frame of analysis [11], [12]. Three samples were obtained for each examined HNT concentration.…”
Section: A Phantoms Preparationmentioning
confidence: 99%
“…However, specifically where the nanoparticle (NP) can extravasate [15]; thus specific functionalization should be tailored [16] upon the study of the NP toxicity profile, as reported in literature for other nanostructured compounds [17]. In most cases gold is the metal of choice for NP manufacturing and the use of gold NP as diagnostic probes has also been demonstrated feasible by preliminary murine studies [18], [19].…”
mentioning
confidence: 99%